2014
DOI: 10.1111/echo.12615
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Contrast Echocardiography to Rule Out Pulmonary Arteriovenous Malformations and Avoid CT Irradiation in Pediatric Patients with Hereditary Hemorrhagic Telangiectasia

Abstract: A low-grade classification (Barzilai 0 or 1) could presumably exclude the presence of PAVMs and allow CT irradiation to be avoided in children and adolescents. The screening algorithm using TTCE first would allow more than 40% of the pediatric patients screened for PAVMs to be spared the radiation dose of CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
2
13
2
Order By: Relevance
“…Especially since HHT is an autosomal dominant disease and as such, half of the offspring of HHT patients will not have HHT. Literature clearly indicates that transthoracic contrast echocardiogram (TTCE) is optimal for detecting PAVMs in adults and probably also in the pediatric HHT population, as some studies have shown . It should also be noted however, that this literature does not take into account non PAVM causes of a right‐to‐left shunt .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially since HHT is an autosomal dominant disease and as such, half of the offspring of HHT patients will not have HHT. Literature clearly indicates that transthoracic contrast echocardiogram (TTCE) is optimal for detecting PAVMs in adults and probably also in the pediatric HHT population, as some studies have shown . It should also be noted however, that this literature does not take into account non PAVM causes of a right‐to‐left shunt .…”
Section: Introductionmentioning
confidence: 99%
“…TTCE requires intravenous access, which can be stressful for children and raise ethical questions on the benefit. Any TTCE showing a shunt greater than a grade 1 will need to be followed up by chest CT scans, even when PAVMs are too small to be embolized …”
Section: Introductionmentioning
confidence: 99%
“…The vascular malformations predispose patients to severe complications due to paradoxical systemic emboli of thrombotic or septic origin, such as stroke and brain abscess [2][3][4][5]. The treatment of choice for PAVMs is transcatheter embolotherapy, although concerns are emerging regarding the long-term consequences of this procedure, especially in children [6].Because of the risk of severe complications, international guidelines recommend screening patients with HHT for the presence of PAVMs at the time of initial clinical evaluation and also after puberty, after pregnancy, within 5 years preceding a planned pregnancy, and otherwise every 5-10 years [7]. Transthoracic contrast echocardiography (TTCE) is the first-line screening technique for the detection of PAVMs in HHT [7].…”
mentioning
confidence: 99%
“…In expert hands, it has excellent sensitivity and negative predictive value for the presence of PAVMs in children and adults. Several grading scales are used in different HHT centres to quantify the pulmonary RLS size [6][7][8]. Microbubbles of air in agitated saline may expose patients with RLS to the risk of cerebral air emboli inducing migraine, blurred vision, numbness and paraesthesia, but these symptoms resolve quickly without residual side effects [9,10].…”
mentioning
confidence: 99%
See 1 more Smart Citation